Business Performance Evaluation Practice in Manufacturing Sector in Latvia - Kotane, Inta; Mietule, Iveta (Ekonomika, 2022)
The manufacturing sector plays an important role in promoting Latvia’s economic growth; this sector is one of the largest sectors of the Latvian economy. Performance can be described as one of the most important categories of economic analysis; however, there is no consensus among researchers on the business performance indicators, their measurement and evaluation methods. The research is based on the analysis of special literature and scientific publications, the evaluation of the financial ratios used in the financial analysis of companies by Latvian institutions, the results of an expert survey, and data from the Official Statistics Portal of Latvia. Literature analysis, expert surveys, correlations, multiple linear regression and forecasting methods were used in the research. The aim of the research is to identify and summarize the performance evaluation practices of manufacturing companies in Latvia. As a result of the research, the business performance evaluation practice in the manufacturing sector was analyzed, the significance of the financial ratios used in the financial analysis in the business performance evaluation in the manufacturing sector and the existence of statistically significant correlations between the financial analysis indicators of manufacturing companies and the key business indicators of manufacturing companies were identified and evaluated.